1989
DOI: 10.1016/s0006-3495(89)82707-9
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced lateral mobility of photosystem I in the photosynthetic membrane

Abstract: Electrophoretic movement of photosystem I (PS I) along the photosynthetic membrane of hypotonically swollen thylakoid vesicles was studied by analyzing the electric field-stimulated delayed luminescence (electrophotoluminescence) emitted from PS I. The electrophoretic mobility was inferred from the differences in electrophotoluminescence (EPL) of the photosynthetic vesicles in presence and absence of trains of low amplitude (<80 V/cm) prepulses of 1 ms duration at 4 ms spacing. The average apparent electric mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…where E u will induce electrophoretic mobility toward the anodic or cathodic sides of the cell, either by direct electrophoretic mobility of the negatively charged components or by electroosmosis, respectively (McLaughlin and Poo, 1981). Though most studies of lateral electrophoretic segregation of charged membrane components have been carried out on adherent cells employing low DC electric fields (e.g., Poo, 1981;Wang et al, 2003), it was shown that a similar segregation phenomenon could be induced in photosynthetic membrane vesicles of a size comparable to that of cells (Brumfeld et al, 1989;Miller et al, 1994), when exposed in suspension to a train of unipolar pulsed electric fields of duration much shorter than the rotational time of the vesicles. Under these conditions the membrane vesicle can be considered to be in a rotational stationary state, at which time the lateral electrophoretic displacement takes place.…”
Section: Possible Mechanisms Underlying the Enhancement Of Adsorptionmentioning
confidence: 99%
“…where E u will induce electrophoretic mobility toward the anodic or cathodic sides of the cell, either by direct electrophoretic mobility of the negatively charged components or by electroosmosis, respectively (McLaughlin and Poo, 1981). Though most studies of lateral electrophoretic segregation of charged membrane components have been carried out on adherent cells employing low DC electric fields (e.g., Poo, 1981;Wang et al, 2003), it was shown that a similar segregation phenomenon could be induced in photosynthetic membrane vesicles of a size comparable to that of cells (Brumfeld et al, 1989;Miller et al, 1994), when exposed in suspension to a train of unipolar pulsed electric fields of duration much shorter than the rotational time of the vesicles. Under these conditions the membrane vesicle can be considered to be in a rotational stationary state, at which time the lateral electrophoretic displacement takes place.…”
Section: Possible Mechanisms Underlying the Enhancement Of Adsorptionmentioning
confidence: 99%
“…Since its discovery in 1971 by Arnold and Azzi (6), electroluminescence has been mostly used as a quantitative probe for precursor concentrations (9-1 1) as a qualitative indicator of electro-genicity (6,10) and as a probe of the electric and diffusion properties of the membrane (12)(13)(14). The temporal and spatial distribution of local fields in the systems used is reflected in the electroluminescence kinetics and polarization and therefore the quantitative interpretation of these properties in terms of electrogenic and thermodynamic parameters is not straightforward and has not been attempted to date.…”
Section: Introductionmentioning
confidence: 99%
“…the bleb inside corresponding to the thylakoid lumen (de Grooth et al 1980b). The asymmetric distribution of the patches explains why orientation effects can occur by gravity (unpublished observations) and by an electric field, as indicated by a field-induced polarization of light scattering (de Grooth et al 1980a), which may provide a more likely explanation for the EL data of Brumfeld et al (1989) than the proposed electrophoretic movement of PSI complexes from one half of the bleb to the other. de Grooth et al 1980a).…”
Section: Rapid and Slow El Component Ps I And Ps Ii Bleb Wall And 'mentioning
confidence: 94%